Genome-Wide Characterization and Expression Profiling of Sugar Transporter Family in the Whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) - Yang, Zezhong; Xia, Jixing; Pan, Huipeng; Gong, Cheng; Xie, Wen; Guo, Zhaojiang; Zheng, Huixin; Yang, Xin; Yang, Fengshan; Wu, Qingjun; Wang, Shaoli; Zhang, Youjun (Frontiers in Physiology, 2017)
Sugar transporters play pivotal roles in the growth, development, and stress responses of phloem-sucking insects, such as the whitefly, Bemisia tabaci. In this study, 137 sugar transporters (STs) were identified based on analysis of the genome and transcriptome of B. tabaci MEAM1. B. tabaci MEAM1 encodes a larger number of STs than other selected insects. Phylogenetic and molecular evolution analysis showed that the 137 STs formed three expanded clades and that the genes in Sternorrhyncha expanded clades had accelerated rates of evolution. B. tabaci sugar transporters (BTSTs) were divided into three groups based on their expression profiles across developmental stages; however, no host-specific BTST was found in B. tabaci fed on different host plants. Mortality rates were significantly increased when seven BTSTs were silenced by oral delivery of its specific dsRNA, especially BTST40 and BTST44 which can significantly reduce the survival of B. tabaci adults at both two and four days upon silencing. These results provide a foundation for further studies of STs in B. tabaci.